OP30 Are the Associations Between Adiposity, Insulin Resistance and Circulating Glucose Concentrations in Childhood Influenced by Ethnicity? Evidence from the Child Heart and Health Study in England (CHASE). (17th September 2012) - Nightingale, CM; Rudnicka, AR; Owen, CG; Sattar, N; Cook, DG; Whincup, PH
Abstract : Background: Ethnic differences in type 2 diabetes risk between South Asians and white Europeans originate before adult life. Although South Asian adults have greater metabolic sensitivity to adiposity this has been little studied in childhood. We have therefore examined the associations between adiposity, insulin and glycated haemoglobin (HbA1c) levels in children of South Asian and white European origin. Data on children of black African-Caribbean origin are also reported. Methods: This was a cross-sectional school-based study of 4633 nine and ten year-old children (response rate 68%) predominantly of South Asian, black African-Caribbean and white European origin. Participants had detailed assessments of adiposity (including body mass index, skinfold thicknesses and fat mass index from bioimpedance) and provided fasting blood samples for assessment of HbA1c and insulin resistance (Homeostatic model assessment-insulin resistance; HOMA-IR). Associations between HOMA-IR (log transformed), HbA1c and adiposity markers were estimated using multilevel linear regression. Results: All adiposity measures were positively associated with insulin resistance in all ethnic groups. However there were clear ethnic differences in the strength of association (p ethnic difference <0.001). The percentage increase in HOMA-IR for a one SD increase in fat mass index was 36.3% (95% CI 32.1%, 40.5%) for South Asians and 25.1% (95% CI 21.1%, 29.3%) for white Europeans; black African-Caribbeans were similar to white Europeans (26.4%, 95% CI 22.5%, 30.4%). All adiposity markers were positively associated with HbA1c in both South Asians and black African-Caribbeans: the percentage increase in HbA1c for a one SD increase in fat mass index in was 0.04% (95% CI 0.02%, 0.06%) in both ethnic groups. However there was no association among white Europeans (0.01%, 95% CI 0.00%, 0.03%). Conclusion: Even in childhood, both insulin resistance and HbA1c levels appear more sensitive to adiposity in South Asians. Among children of black African-Caribbean origin, HbA1c levels but not insulin resistance appear more sensitive to adiposity. The reasons for these differences in sensitivity to adiposity need to be understood. The results imply that early prevention of childhood obesity among South Asians and black African-Caribbeans is a particular priority for future control of type 2 diabetes in these high risk ethnic groups.